The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5539/jas.v7n11p132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extrusion Pretreatment on Enzymatic Hydrolysis of Miscanthus for the Purpose of Ethanol Production

Abstract: Lignocellulosic biomass can be converted to energy via several routes. One of them is hydrolysis to sugars with subsequent transformation to fuels and chemicals. Due to the crystalline structure of lignocellulose, pretreatment is a prerequisite to achieving increased enzymatic hydrolysis' rates. The objective of this study was to determine the optimum extrusion operating conditions for glucose and xylose production from Miscanthus. Extrusion was conducted in a high shear extruder (single screw type) with compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…The high sugar recovery due to extrusion pretreatment is related to fibrillation, the increase in surface area [79-81, 86, 87] and pore size [103], which facilitate the access of enzymes to cellulose. Some authors have reported that the crystallinity, which confers resistance to enzymatic hydrolysis, was not significantly reduced in extruded biomass [79,102] and therefore was not related to the increase in biomass digestibility.…”
Section: Extrusion Processmentioning
confidence: 99%
“…The high sugar recovery due to extrusion pretreatment is related to fibrillation, the increase in surface area [79-81, 86, 87] and pore size [103], which facilitate the access of enzymes to cellulose. Some authors have reported that the crystallinity, which confers resistance to enzymatic hydrolysis, was not significantly reduced in extruded biomass [79,102] and therefore was not related to the increase in biomass digestibility.…”
Section: Extrusion Processmentioning
confidence: 99%
“…Briefly, pretreatment by milling aims to reduce the particle size and increase the surface area of the biomass to improve enzymatic saccharification in a later step, 53,54 while extrusion is used to reduce particle size (by the mechanical action of discs combined with temperature) and results in physical and chemical changes in biomass 55 . At industrial scale, biomass should be used as it is received from sugarcane or corn processing mills, without any further milling, to save the prohibitive cost incurred in milling or size reduction.…”
Section: General Routes Of Biomass Processingmentioning
confidence: 99%
“…Ha sido reportado que la extrusión semi-seca genera un aumento significativo en la digestibilidad de DIVMS y DIVFDN del pasto Pheleum pratense L., debido probablemente a que dicho proceso afecta la estructura física y química de esta gramínea (29). Otros autores han encontrado, así mismo, aumentos en la fermentabilidad de otras gramíneas forrajeras luego de su procesamiento mediante diferentes tipos de extrusores, expresada está en el incremento en el rendimiento de diferentes monosacáridos producto de la degradación de la celulosa y hemicelulosa (glucosa, xilosa, arabinosa) (30,31).…”
Section: Discusionunclassified